New anti-bacterial halogenated tricyclic sesquiterpenes from Bornean Laurencia majuscula (Harvey) Lucas - Takashi Kamada; Phan, Chin Soon; Charles Santhanaraju Vairappan (Taylor & Francis, 2019)
Three new halogenated tricyclic sesquiterpenes, omphalaurediol (1), rhodolaurenones B (2) and C (3) were isolated together with nine known haloganated sesquiterpenes such as rhodolaurenone A (4), rhodolaureol (5), isorhodolaureol (6), (−)-laurencenone D (7), elatol (8), (+)-deschloroelatol (9), cartilagineol (10), (+)-laurencenone B (11) and 2-chloro-3-hydroxy-α-chamigren-9-one (12) from a population of Bornean red algae Laurencia majuscula. The structures of three new metabolites were determined based on their spectroscopic data (IR, 1D and 2D NMR, and MS). These compounds showed antibacterial activity against three human pathogenic bacteria (Escherichia coli, Salmonella typhi and Vibrio cholera).